2000
DOI: 10.1007/s002470000322
|View full text |Cite
|
Sign up to set email alerts
|

Importance of hypoxic/ischemic conditions in the development of cerebral lenticulostriate vasculopathy

Abstract: LSV has varied clinical associations. The common association with hypoxic/ischemic conditions and the progressive changes seen in 12 patients with cardiac and pulmonary disease suggest that postnatal hypoxia/ischemia is an important etiologic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 0 publications
6
57
2
Order By: Relevance
“…Extending the recent observation of El Ayoubi et al 12 (28 of 70 neonates with LSV had either intraventricular hemorrhage (IVH) or periventricular leucomalacia (PVL), in this study, through the use of multivariate logistic regression, the reader will find we have confirmed that a statistically significant and unconfounded relationship exists between neonatal IVH and LSV, the latter being a lesion that we, as did Hemachandra et al 11 and Coley et al, 10 have found to be more common than reported in the older medical literature.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Extending the recent observation of El Ayoubi et al 12 (28 of 70 neonates with LSV had either intraventricular hemorrhage (IVH) or periventricular leucomalacia (PVL), in this study, through the use of multivariate logistic regression, the reader will find we have confirmed that a statistically significant and unconfounded relationship exists between neonatal IVH and LSV, the latter being a lesion that we, as did Hemachandra et al 11 and Coley et al, 10 have found to be more common than reported in the older medical literature.…”
Section: Introductionsupporting
confidence: 79%
“…However, it may be that the growing awareness of its presence and the advent of more sophisticated cranial imaging devices with improved resolution may account for some, if not all, of the reported increase in LSV prevalence. For example, in 2000, Coley et al 10 reported that more than 4.2% of neonates in their study were found to have the lesion. More recently, Hemachandra et al, 11 in a retrospective study published in this Journal, also found that LSV was not uncommon (prevalence of 4.6% (21 of 453 reviewed cranial images)).…”
Section: Introductionmentioning
confidence: 95%
“…By definition, LSV consists of bright, echogenic, linear blood vessels in the basal ganglia and thalami. Neuropathological correlates of LSV include thickened and hypercellular blood vessel walls having intramural and perivascular mineralization, 30 as well as adventitial or subendothelial deposits of amorphous, basophilic material in small-and medium-sized arteries. 31 Of interest, LSV was first reported in the 1960s after a congenital rubella epidemic in Philadelphia.…”
Section: Lenticulostriate Vasculopathymentioning
confidence: 99%
“…1,2,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Basal ganglia hemorrhage results from periventricular hemorrhagic infarction or hemorrhagic necrosis. In preterm infants <28 weeks, diffuse caudate hemorrhage is difficult to differentiate from hemorrhage in the germinal matrix over the body of the caudate nucleus (grade I).…”
Section: Introductionmentioning
confidence: 99%